A Note respecting the Sculptured Cross at St Vigeans, near Arbroath; of which casts by Mr Henry Laing, Seal Engraver, were exhibited (Proceedings of the Society of Antiquaries of Scotland, 1855)
Descriptions of four crosses found in St. Vigeans. Particular attention is paid to the carvings and condition of the crosses. The author argues that casts should be taken of these stone crosses now so that their design can be preserved in case the originals deteriorate. It was agreed by the members present that the Society should ask Mr. Henry Laing to produce casts from the crosses and also encourage the landowners to conserve the monuments.